The Role of Anatomy Education in Facilitating Multidisciplinary Collaboration in the Treatment of Musculoskeletal Conditions an Example from Australia - Giuriato,Rosemary (Sociedad Chilena de Anatomía, 2016)
Emerging changes to the healthcare system are promoting the adoption of an integrative medicine and a more patient-centred approach to healthcare. A multidisciplinary approach to the management of musculoskeletal conditions has a potential to ease the pressure off the emergency public health care system. Interprofessional collaboration in health care is paramount for this synergism to occur. It is crucial that treatment options be consistent and transparent across different health professions in order for optimum patient centred care. Using the Australian educational and health setting as an example, it is argued in this paper that anatomy education could play an important role in facilitating this consistency and transparency. The first decisive step in this process would be to review the alignment of anatomy syllabi across the academic programs of different health professions. The review and comparison of anatomy content taught across the different health professional curricula should expedite the acceptance of one profession by another. This alignment of anatomy teaching would aid interprofessional relations and ultimately collaboration, beginning from education of students through to professional practice and encompassing accreditation guidelines.